2009
DOI: 10.1111/j.1365-2559.2009.03310.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma protuberans: clinical, pathological, and genetic (COL1A1‐PDGFB ) study with therapeutic implications

Abstract: The COL1A1-PDGFB fusion was present in all histological subtypes of DFSP, but not all cases expressed the fusion transcript. No association was observed between different COL1A1 breakpoints and clinicopathological parameters. Imatinib mesylate can be useful in locally advanced tumours and metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 66 publications
4
62
0
8
Order By: Relevance
“…Detection of the COL1A1/PDGFB transcript varied from 74 to 96% (Maire et al, 2002;Gokden et al, 2003;Terrier-Lacombe et al, 2003;Llombart et al, 2009;Patel et al, 2008). In the present study, in which we include 63 cases previously published (Llombart et al, accepted for publication), we detected the COL1A1/PDGFB transcript in 80% of DFSP.…”
Section: Comparison Between Rt-pcr and Fish Techniquessupporting
confidence: 49%
See 2 more Smart Citations
“…Detection of the COL1A1/PDGFB transcript varied from 74 to 96% (Maire et al, 2002;Gokden et al, 2003;Terrier-Lacombe et al, 2003;Llombart et al, 2009;Patel et al, 2008). In the present study, in which we include 63 cases previously published (Llombart et al, accepted for publication), we detected the COL1A1/PDGFB transcript in 80% of DFSP.…”
Section: Comparison Between Rt-pcr and Fish Techniquessupporting
confidence: 49%
“…RNA was extracted using 1 ml of Trizol Reagent (Invitrogene, Carlsbad, CA) following the manufacturer's instructions. RT-PCR was carried out as previously described (Llombart et al, 2009). …”
Section: Identification Of Col1a1/pdgfb Fusion Transcriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different results using RT-PCR amplification techniques have been reported. A recent work including 20 cases of DFSP using frozen tissue samples detected 16 positive cases from the 18 (89%) in which RNA could be obtained [23]. Other studies using paraffin-embedded tissue showed variable results from 74% to 96% [17,24,25] of positive cases.…”
Section: Discussionmentioning
confidence: 97%
“…This is the mechanism being targeted with small molecule tyrosine kinase inhibitor therapy such as imatinib. 25,34,37 Furthermore, detection of this chromosomal aberration by FISH (Fluorescence In Situ Hybridization) represents an invaluable diagnostic tool, particularly in cases of DFSP-FS and other unusual variants, since all of which will exhibit the cytogenetic signature 18,19,21,25,38,39 . Interestingly, this same signature cytogenetic aberration is present in the childhood tumor Giant Cell Fibroblastoma (GCF), with known reported cases showing hybrid DFSP/GCF features.…”
Section: Clinical Featuresmentioning
confidence: 99%